Peningkatan Keterampilan Sosial Peserta Didik Melalui Model Pembelajaran Time Token dengan Media Puzzle - Anggraini, Novia Septi; Sukowiyono, Sukowiyono; Untari, Sri (Universitas Negeri Malang, 2021)
This study aimed to analyze the application of the time token learning model with puzzle media in Pancasila and Civic Education learning and the enhancement of students' social skills after applying the time token learning model with puzzle media. The study used a qualitative approach with the classroom action research type. The data were described in a quantitative descriptive manner. The study used two cycles that consisted of planning, action, observation, and reflection. Data collection techniques had to be done through observation, reflection, and documentation. Data analysis was carried out interactively. The application of the time token learning model with puzzle media was carried out by conveying the objectives, explaining the material meaning of the position and function of Pancasila, the procedure for implementing the model, forming groups, giving speech coupons, distributing puzzles, combining puzzles, analyzing puzzle results, presenting and providing responses. The improvement of students' social skills after applying the time token learning model with puzzle media was proven before the action that passed the Minimum Graduation Criteria (KKM) by 45.14 percent, after being given the first cycle it became 65.50 percent and in the second cycle, it became 79.96 percent.